The relationship between voluntary product (re) formulation commitments and changes in the nutritional quality of products offered by the top packaged food and beverage companies in Canada from 2013 to 2017 - Laura Vergeer; Mavra Ahmed; Lana Vanderlee; Christine Mulligan; Madyson Weippert; Beatriz Franco-Arellano; Kacie Dickinson; Jodi T. Bernstein; Marie-Ève Labonté; Mary R. L'Abbé (BMC, 2022)
Abstract Background Food companies shape Canada's food supply through voluntary actions and commitments concerning product (re)formulation; however, the extent that these initiatives translate into actual improvements in nutritional quality is unclear. This study examined changes in the nutritional quality of products offered by the top 22 packaged food and beverage companies in Canada from 2013 to 2017, in relation to the strength of their product (re) formulation actions and commitments. Methods The Food Company Reformulation (FCR) scoring tool was used to quantify the strength of companies' reported recent actions and commitments to reduce energy and nutrients of concern in their products, with higher scores signifying stronger voluntary actions/commitments. Nutritional information for products was sourced from the University of Toronto FLIP 2013 (n = 6490) and 2017 (n = 8277) databases (n = 4074 matched products). Changes in product healthfulness were assessed using the Health Star Rating (HSR) system (with higher HSRs denoting healthier products) and calories, sodium, saturated fat, trans fat, and total and free sugar levels per 100 g/mL. Generalized estimating equations examined changes in nutritional quality in relation to FCR scores. Results Overall, mean HSRs increased significantly for 5 companies' product portfolios and were reduced in 1 company's product portfolio. There were significant reductions in calories, sodium, saturated fat in 2 companies' portfolios and increases in 4, 3, and 8 companies' portfolios, respectively. Trans fats increased significantly in 2 companies' portfolios. Total and free sugars decreased significantly in 4 and 5 companies' portfolios, respectively, and increased in 1 company's portfolio. There was little change in the healthfulness of matched products. Higher FCR scores were not associated with greater increases in HSRs, or reductions in calories or nutrient amounts. FCR scores were negatively associated with HSRs and positively associated with total and free sugars. No relationship was observed between FCR scores and calories, sodium, saturated fat or trans fat. Conclusions Reporting stronger voluntary product (re) formulation actions and commitments was not associated with greater improvements in the healthfulness of products offered by Canada's leading packaged food and beverage companies from 2013 to 2017, suggesting a need for stronger industry initiatives or mandatory government interventions to improve the healthfulness of the food supply.